Resisting change: the influence of luminance changes on visual marking and the preview benefit. - Watson, D; Braithwaite, J; Humphreys, G (2008)
Visual search can benefit when one set of distractors is presented as a preview, prior to the appearance of the second set of distractors plus the target (Watson and Humphreys, 1997). It has been shown that changing the shape of the old, previewed stimuli when the new items appear causes the old stimuli to recompete for selection with the new ones. In contrast, changing the luminance or color of the old stimuli has no detrimental effects. Here, we present five experiments that reassessed the effect of luminance changes in preview search. We show (1) that preview search is remarkably resistant to large changes in the absolute luminance of the old stimuli, even when those changes would ordinarily be sufficient to signal the appearance of a new object and draw attention (Experiments 1 and 2), and (2) that resistance to luminance changes can be bolstered by feature-based inhibitory processes (Experiments 3-5). These findings are discussed in terms of the possible ecological properties of time-based visual selection and possible mechanisms underlying the preview benefit.